Age at menarche and risks of coronary heart and other vascular diseases in a large UK cohort. - Canoy, D; Beral, V; Balkwill, A; Wright, F; Kroll, M; Reeves, G; Green, J; Cairns, B (2015)
BACKGROUND: Early menarche has been associated with increased risk of coronary heart disease (CHD), but most studies were relatively small and could not assess risk across a wide range of menarcheal ages; few have examined associations with other vascular diseases. We examined CHD, cerebrovascular disease, and hypertensive disease risks by age at menarche in a large prospective study of UK women. METHODS AND RESULTS: In 1.2 million women (mean±SD age, 56±5 years) without previous heart disease, stroke, or cancer, menarcheal age was reported to be 13 years by 25%, ≤10 years by 4%, and ≥17 years by 1%. After 11.6 years of follow-up, 73 378 women had first hospitalization for or death from CHD, 25 426 from cerebrovascular disease, and 249 426 from hypertensive disease. Using Cox regression, we calculated relative risks for each vascular outcome by single year of menarcheal age. The relationship was U-shaped for CHD. Compared with women with menarche at 13 years, the adjusted relative risk for CHD for menarche at ≤10 years of age was 1.27 (95% confidence interval, 1.22-1.31; P<0.0001) and for menarche at ≥17 years of age was 1.23 (95% confidence interval, 1.16-1.30; P<0.0001). U-shaped relationships were also seen for cerebrovascular and hypertensive disease, although the magnitudes of these risks for early and late menarche were smaller than those for CHD. CONCLUSIONS: In this cohort, the relation of age at menarche to vascular disease risk was U shaped, with both early and late menarche being associated with increased risk. Associations were weaker for cerebrovascular and hypertensive disease than for CHD.